2016
DOI: 10.1155/2016/4070251
|View full text |Cite
|
Sign up to set email alerts
|

A Joint Scheduling Optimization Model for Wind Power and Energy Storage Systems considering Carbon Emissions Trading and Demand Response

Abstract: To reduce the influence of wind power random on system operation, energy storage systems (ESSs) and demand response (DR) are introduced to the traditional scheduling model of wind power and thermal power with carbon emission trading (CET). Firstly, a joint optimization scheduling model for wind power, thermal power, and ESSs is constructed. Secondly, DR and CET are integrated into the joint scheduling model. Finally, 10 thermal power units, a wind farm with 2800 MW of installed capacity, and 3 × 80 MW ESSs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…DSM mechanism based on price can effectively motivate electricity consumers to adjust their inherent mode of using 2 Mathematical Problems in Engineering electricity and to change their behaviors with the smart grid system through following varying price signals of electricity [2]. For example, an individual customer may change his/her air conditioner temperature or reprogram the charging process of his/her electric car or/and battery banks during the valley hours, while his/her watt hour bill of electricity is the lowest.…”
Section: Background and Motivation In 2007 The United Statesmentioning
confidence: 99%
“…DSM mechanism based on price can effectively motivate electricity consumers to adjust their inherent mode of using 2 Mathematical Problems in Engineering electricity and to change their behaviors with the smart grid system through following varying price signals of electricity [2]. For example, an individual customer may change his/her air conditioner temperature or reprogram the charging process of his/her electric car or/and battery banks during the valley hours, while his/her watt hour bill of electricity is the lowest.…”
Section: Background and Motivation In 2007 The United Statesmentioning
confidence: 99%
“…Reference [16] proposes an approach to integrate power to gas technology to the multi-source MG including wind power, electric boiler, micro turbine and gas boiler. In [17], the energy storage systems and DR are introduced to the traditional scheduling model of wind and thermal power with carbon emission trading for reducing the influence of random nature of wind power on system operation. From the above literature review, it can be observed that there is a pressing requirement for an optimal operation of MG considering the RESs, BES systems, EVs and DR [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [16] proposes an approach to integrate power to gas technology to the multi-source MG including wind power, electric boiler, micro turbine and gas boiler. In [17], the energy storage systems and DR are introduced to the traditional scheduling model of wind and thermal power with carbon emission trading for reducing the influence of random nature of wind power on system operation. From the above literature review, it can be observed that there is a pressing requirement for an optimal operation of MG considering the RESs, BES systems, EVs and DR.…”
Section: Introductionmentioning
confidence: 99%